Toward Understanding the Role of Aryl Hydrocarbon Receptor in the Immune System: Current Progress and Future Trends. (6th January 2014) - Hanieh, Hamza
Abstract : The immune system is regulated by distinct signaling pathways that control the development and function of the immune cells. Accumulating evidence suggest that ligation of aryl hydrocarbon receptor (Ahr), an environmentally responsive transcription factor, results in multiple cross talks that are capable of modulating these pathways and their downstream responsive genes. Most of the immune cells respond to such modulation, and many inflammatory response-related genes contain multiple xenobiotic-responsive elements (XREs) boxes upstream. Active research efforts have investigated the physiological role of Ahr in inflammation and autoimmunity using different animal models. Recently formed paradigm has shown that activation of Ahr by 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) or 3, 3′-diindolylmethane (DIM) prompts the differentiation of CD4 + Foxp3 + regulatory T cells (Tregs) and inhibits T helper (Th)-17 suggesting that Ahr is an innovative therapeutic strategy for autoimmune inflammation. These promising findings generate a basis for future clinical practices in humans. This review addresses the current knowledge on the role of Ahr in different immune cell compartments, with a particular focus on inflammation and autoimmunity.